Strategi Organisasi Dalam Memberdayakan Karyawan Milenial Untuk Menjadi Unit Kerja Percontohan - Inta Hartaningtyas Rani; Ali Chaerudin (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2021)
This study analyzes the HRD strategy, especially in the recruitment system, empowerment (human development) effort, performance appraisal, and rewards program. The employee empowering process of BRI Tangcity as the best service excellence branch is deeply examined to formulate the HRD strategies in empowering millennial employees (80% of BRI Tangcity employees are millennials). This study uses a comparative descriptive research model through in-depth interview techniques in gaining information related to HRD strategies and the achievement of